2007
DOI: 10.2527/jas.2006-231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental iron on finishing swine performance, carcass characteristics, and pork quality during retail display1

Abstract: Crossbred pigs (n = 185) were used to test the effects of dietary Fe supplementation on performance and carcass characteristics of growing-finishing swine. Pigs were blocked by BW, allotted to pens (5 to 6 pigs/pen), and pens (5 pens/block) were allotted randomly to either negative control (NC) corn-soybean meal grower and finisher diets devoid of Fe in the mineral premix, positive control (PC) corn-soybean meal grower and finisher diets with Fe included in the mineral premix, or the PC diets supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
3
15
0
2
Order By: Relevance
“…Saddoris et al (2003) observed that supplementing pig diets with 90 ppm Fe did not affect average backfat depth and longissimus muscle area, whereas Apple et al (2007) observed a linear increase in 10 th -rib fat depth as supplemental Fe from 50 to 150 ppm in diets. Our study showed a favourable effect of L-carnitine+Fe (as Fe-AA complex) supplement on the quality of pork carcasses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saddoris et al (2003) observed that supplementing pig diets with 90 ppm Fe did not affect average backfat depth and longissimus muscle area, whereas Apple et al (2007) observed a linear increase in 10 th -rib fat depth as supplemental Fe from 50 to 150 ppm in diets. Our study showed a favourable effect of L-carnitine+Fe (as Fe-AA complex) supplement on the quality of pork carcasses.…”
Section: Discussionmentioning
confidence: 99%
“…Daily gains and feed conversion did not depend on 30 to 120 ppm Fe in the pig diet either (Yu et al 2000, Saddoris et al 2003. Apple et al (2007) found that 50 to 150 ppm Fe supplement in the grower and finisher diet increased the daily gains of growing pigs (55-68 kg BW), while not having any effect on growth performance in the finishing pigs. On the other hand, Liao et al (2005) found a rise of growth performance in 50 to 100 kg BW pigs obtaining the chelated Fe (1 g/kg diet).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On addition, the supplementation with Selenium can contribute for a better meat stability due to its protective action in the membranes, preserving it against the oxidizing agents (Calvo et al, 2016). The color of the pigment myoglobin is also dependent on the lipid oxidation degree in the meat (Apple et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The applicant submitted four published papers (one in laying hens and three in pigs). The study in laying hens (Park et al, 2004) was not considered since product identity to that under application could not be established; the experiment with pigs for fattening (Apple et al, 2007) also could not be considered owing to weaknesses in design and reporting. The remaining two studies in piglets (Yu et al, 2000;Grela et al, 2005) support the general knowledge that iron from iron chelate of amino acids, hydrate, is a source of bioavailable dietary iron.…”
Section: Efficacymentioning
confidence: 99%